2013
DOI: 10.1111/lam.12095
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a dual fluorescence method in detecting the viability of overwintering cyanobacteria

Abstract: Significance and Impact of the Study: This study established the efficacy of the dual fluorescence method in evaluating the viability of cyanobacteria under chill-light stress. The results provided the direct evidence for acquired chill-light tolerance and the viability of overwintering Microcystis colonies. Such information can be useful in prediction of cyanobacterial blooms. AbstractChill in the light is the major environmental stress that cyanobacteria encounter in winter. Cyanobacterial cells may acquire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Studies using Synechocystis sp. strain PCC 6803 (Synechocystis 6803) showed that preconditioning at a low temperature, such as 15°C, could greatly enhance its survivability under long-term chill (5°C)-light stress (7,8). This finding suggests that cyanobacteria acquire the capability to overwinter in late autumn and early winter.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Studies using Synechocystis sp. strain PCC 6803 (Synechocystis 6803) showed that preconditioning at a low temperature, such as 15°C, could greatly enhance its survivability under long-term chill (5°C)-light stress (7,8). This finding suggests that cyanobacteria acquire the capability to overwinter in late autumn and early winter.…”
mentioning
confidence: 74%
“…In previous reports, we showed that ␣-tocopherol, which is membrane localized, is essential for the acquired chill-light tolerance (ACLT) of cyanobacteria (7) and that accumulation of RNAbinding protein 1 (Rbp1) leads to the formation of overwintering capability of cyanobacteria (8,12). Nonetheless, information about the biology of overwintering cyanobacteria is still very limited.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, SYTO® 9 is used in conjunction with propidium iodide (PI) as a dual-stain assay in which SYTO® 9 causes viable cells to fluoresce in the green spectrum and PI causes non-viable cells to fluoresce in the red spectrum. This assay has previously been used in unicellular cyanobacteria [89], however our research group determined that PI binds to both viable and non-viable cells in filamentous cyanobacteria and cannot accurately quantitate non-viable cells in the strains used in this study [36]. We later determined that SYTO® 9 does stain viable filamentous cyanobacteria cells as expected and was used to monitor growth in this study [38].…”
Section: Methodsmentioning
confidence: 98%
“…Fluorescence microscopy was carried out using a Zeiss AxioImager Z1 microscope following staining of samples with Cyto9 and propidium iodide (Invitrogen), using FITC (490/530 Ex/Em) and TRITC (547/572 Ex/Em) filters. Samples were prepared by mixing 1 ml of the suspension with 3μl of the combined (premixed) stain in sterile Eppendorf tubes and incubating for 15 minutes (Zhu and Xu, 2013). Stained suspensions were centrifuged for 10 minutes and rinsed three times in 10 mM NaCl in order to remove the stain and hence avoid artefacts due to cell death post-staining.…”
Section: Cell Viability In Influent and Effluentsmentioning
confidence: 99%